Distribution Characteristics of SOC, STN, and STP Contents Along a Slope Aspect Gradient of Loess Plateau in China - Liu, Minxia; Yu, Ruixin; Li, Liang; Xu, Lu; Mu, Ruolan; Zhang, Guojuan (Frontiers in Soil Science, 2021)
Semi-arid of Loess Plateau associated with complex topography are characterized by large variability in the spatial distribution of SOC (soil organic carbon)，STN (soil total nitrogen) and STP (soil total phosphorus). Slope aspects as an important topographical factor has an important influence on SOC, STN and STP. In this study, the effects of slope aspects and depths on SOC, STN and STP were quantified in disturbed restoration region of Gaolan County. Soil samples were collected at 0-10, 10-20, 20-40, 40-60, 60-80 and 80-100 cm on southern, southwestern, western, northwestern and northern slope aspects of three hills. A total of 120 soil profiles and 720 soil samples were analyzed. Results showed that the SOC, STN and STP content varied from 1.65-12.87 g/kg, 0.45-1.53 g/kg and 0.07-0.78 g/kg, and the SOCD, STND and STPD at 0-100 cm varied from 3.9-9.5 kg/m2, 0.58-1.35 kg/m2, 0.33-0.56 kg/m2, increased from the southern to northern slope aspects. The SOC, STN and STP contents and SOCD, STND and STPD were mainly in the 0-60 and 60-100 cm soil layers. Vertical descent rate, γSOC> γSTN>γSTP for both content and density. For a single soil nutrient, the decline rate of its content and density on the northern slope aspect is greater than that on the southern slope aspect, that is γN> γ All >γS. The correlation degree between soil properties and SOC, STN content were above medium, the overall correlation with STP content was low. Among them, soil temperature (ST), soil density (ρ) and soil water content (θ) were significantly correlated with SOC, STN content on between the southern and northern slope aspects, and could be regarded as the main influencing factors, pH with STP content have a high correlation. These results confirmed that topography (slope aspects) was the most significant factor controlling the distribution patterns of SOC, STN and STP in hill ecosystems. Overall, northern slope aspect (vs. southern slope aspect) was more favorable to the preservation of SOC, STN and STP. Accordingly, in the Loess Plateau and similar fragile environments, soil nutrient protection and vegetation restoration are selective to some extent.